Ahkam “Dun” wa Dilalatuha As-Siyaqiyah - Aboaws Ibrahim Alshamsan (el Harakah: Jurnal Budaya Islam, 2016)
تبين لنا من هذا البحث أن (دون) ظرف مبهم منصرف كثير ملازمة الظرفية غير أنه نقل للاسمية فأخبر به ووصف به بمعنى الشيء المنحط عن غيره لأن دلالة (دون) هي تقصير عن الغاية المكانية الحسية أو المعنوية، واستعمل (دون) اسم فعل أمر بمعنى خذ المتعدي أو بمعنى توقف أو تأخر اللازم، واتصفت جملته بالجمود فلا يتعدى مفعوله عليه، وأخذ من دون اسم تفضيل للدلالة على تفاوت المكان أو المكانة، واستعملت (دون) في السياق بدلالات وظيفية مختلفة فجاءت بمعنى (لا)، و(قبل)، و(قُدّام)، و(تحت)، و(غير) و(من غير)، وتتركب (دون) مع حرف الجر (من) لتكون بمعنى (غير)، و(قبل)، و(تحت)، و(لا)، و(سوى)، وتتركب (دون) مع حرف الجر الباء ليكون بمعنى (غير)، و(أقل). ويستفاد من هذا أنه لك استعمال (دون) أو (من دون) أو (بدون) إن أردت معنى (غير) أو (أقل).  It appears from this research that (Doon) is a vague adverb, and it always stays as an adverb. However, it has been also used as a noun. Therefore it could be used as a predicate. (Doon) describes things that are less than the others, either physically or socially. In addition, it is likely used as a command verb in the meaning of take or stop. The sentence that (Doon) comes in, is always in a specific order. (Doon) can also be used to express preference or disparity of places and ranks and it comes in the meaning of (not), (before), (in front), (below), (other than) and (without) depending on the context. (Doon) is an idiom when it combines with the preposition (from) in the meaning of (other than), (before), (under), (not) and (except), it also combines with the preposition (with) in the meaning of (other than), (before), (below), (not) and (except). Finally, you can use (Doon) or (Mn Doon) or (Bedoon) in the meaning of (other than) or (below).